Sincerity in Politics and International Relations - Baiasuis, Sorin; Loriaux, Sylvie 1972- (Taylor and Francis, 2016)
This work examines concept of sincerity in politics and international relations in order to discuss what we should expect of politicians, within what parameters should they work, and how their decisions and actions could be made consistent with morality. The collection features an international cast of authors who specialize in the topic of sincerity in politics and international relations. Each chapter will be focused on a contemporary issue in politics and international relations, including corruption, public hypocrisy, cynicism, trust, security, policy formulation and decision-making, political apology, public reason, denial and self-deception,and will argue against the background of a Kantian view of sincerity as unconditional. Focusing on sincerity bearing on political actions, practices, and institutions at national and international level, the collection will include an introduction by the editors that will serve to place the contributions in the context of ongoing contemporary debates on sincerity in politics and international theory. Offering a significant comprehensive outlook on the practical limits of sincerity in political affairs, this work will be of great interest to students and scholars alike